2015
DOI: 10.1001/jamapediatrics.2014.1900
|View full text |Cite
|
Sign up to set email alerts
|

Violent Reinjury and Mortality Among Youth Seeking Emergency Department Care for Assault-Related Injury

Abstract: IMPORTANCE Violence is a leading cause of morbidity and mortality among youth, with more than 700 000 emergency department (ED) visits annually for assault-related injuries. The risk for violent reinjury among high-risk, assault-injured youth is poorly understood. OBJECTIVE To compare recidivism for violent injury and mortality outcomes among drug-using, assault-injured youth (AI group) and drug-using, non–assault-injured control participants (non-AI group) presenting to an urban ED for care. DESIGN, SETTI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
150
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(161 citation statements)
references
References 38 publications
9
150
1
1
Order By: Relevance
“…The ED is an important implementation setting for prevention, in part because a large proportion of patients will experience a subsequent assault-related injury or premature death within a few years of a treated injury ( 6 , 7 ). For example, one study compared persons aged 14–24 years who sought treatment in the ED and reported substance use in the 6 months before the visit.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ED is an important implementation setting for prevention, in part because a large proportion of patients will experience a subsequent assault-related injury or premature death within a few years of a treated injury ( 6 , 7 ). For example, one study compared persons aged 14–24 years who sought treatment in the ED and reported substance use in the 6 months before the visit.…”
Section: Discussionmentioning
confidence: 99%
“…For example, one study compared persons aged 14–24 years who sought treatment in the ED and reported substance use in the 6 months before the visit. Of the young persons who were seen initially for an assault-related injury, 36.7% were seen again for an assault-related injury within 24 months, compared with 22.4% of the young persons initially seen for other conditions (e.g., unintentional injury or illness) ( 6 ). …”
Section: Discussionmentioning
confidence: 99%
“…Beyond being male, part of a racial minority group and uninsured, violent injury and homicide in this group may be predicted by such factors as being part of high-risk social networks, recidivism, delinquency and drug usage 8 13–19. However, the risk of death after non-GSW assault appears to be constant, whereas the deaths in the GSW cohort occurred differentially in the early period after discharge.…”
Section: Discussionmentioning
confidence: 99%
“…The need for early diagnosis and treatment may be highest in adolescents with a history of physical peer violence, a population at high risk for future trauma 25,26 . A history of physical peer violence is a strong predictor of PTSD symptoms in adults and adolescents 2,3,27,28 .…”
Section: Introductionmentioning
confidence: 99%